In Situ Investigation of the Rapid Solidification Behavior of Intermetallic γ‐TiAl‐Based Alloys Using High‐Energy X‐Ray Diffraction. Issue 11 (3rd July 2021) - Graf, Gloria; Rosigkeit, Jan; Krohmer, Erwin; Staron, Peter; Krenn, Raimund; Clemens, Helmut; Spoerk-Erdely, Petra
Abstract : Representing an attractive new processing method, additive manufacturing can be used to manufacture parts made of γ‐TiAl‐based alloys for high‐temperature applications. However, in terms of nucleation during rapid solidification and subsequent solid‐state phase transformations, the process is not yet fully understood, and research is still going on. This article focuses on a setup to study solidification processes during laser melting via in situ high‐energy X‐ray diffraction at a synchrotron radiation source. To create conditions similar to those encountered in powder bed‐based additive manufacturing processes, such as electron beam melting or selective laser melting, a thin platelet is laser‐melted on its upper edge. Phase transitions are measured simultaneously via high‐energy X‐ray diffraction in transmission geometry. The use of a thin platelet instead of the usual powder bed precludes the unfavorable contribution of solid phases from surrounding powder particles to the diffraction signal. First results of the in situ high‐energy X‐ray diffraction experiment on a Ti–48Al–2Nb–2Cr (in at%) alloy prove the applicability of the used setup for an accurate tracing of phase transformations upon rapid solidification. Abstract : In situ high‐energy X‐ray diffraction investigations are conducted to study phase transformations during rapid solidification. The used experimental setup creates conditions similar to powder bed‐based additive manufacturing processes. A thin platelet of an intermetallic γ‐TiAl‐based alloy is laser‐melted on its upper edge and phase transformations during solidification can directly be detected.